Commonly Used Preparations for Colonoscopy: Efficacy, Tolerability and Safety – A Canadian Association of Gastroenterology Position Paper - Alan Barkun; Naoki Chiba; Robert Enns; Margaret Marcon; Susan Natsheh; Co Pham; Dan Sadowski; Stephen Vanner (Canadian Journal of Gastroenterology)
INTRODUCTION: The increased demand for colonoscopy, coupled with the introduction of new bowel cleansing preparations and recent caution advisories in Canada, has prompted a review of bowel preparations by the Canadian Association of Gastroenterology.